CRITERIA AND LEVELS OF ACTIVATION OF COGNITIVE ACTIVITY OF STUDENTS - O.V. Katerusha (Academy of Cognitive and Natural Sciences, 2009)
The article deals with criteria and levels of students' activitation in terme of cognitivactivity.